Interaction mechanism of kafirin with ferulic acid and tetramethyl pyrazine: Multiple spectroscopic and molecular modeling studies. (30th November 2021) - Zhu, Lin; Song, Xuebo; Pan, Fei; Tuersuntuoheti, Tuohetisayipu; Zheng, Fuping; Li, Qing; Hu, Siqi; Zhao, Feifei; Sun, Jinyuan; Sun, Baoguo
Graphical abstract: Highlights: The first report to predict the three-dimensional structure of kafirin. The binding of kafirin and FA/TMP is mainly a static quenching procedure. The binding with FA and TMP decreased the α-helix content of kafirin. Hydrogen bonds and hydrophobic interactions are the main forces forming complexes. The binding with FA/TMP made the structures of α-, β- and δ-kafirin more compact. Abstract: Ferulic acid (FA) and tetramethyl pyrazine (TMP) are intrinsic bioactive compounds in baijiu, and kafirin is the major protein of sorghum, which is the raw material of baijiu. In this study, the interactions of kafirin-FA and kafirin-TMP were investigated by multiple spectroscopic and molecular modeling techniques. Fluorescence spectra showed that intrinsic fluorescence of kafirin drastically quenched because of the formations of kafirin-FA and kafirin-TMP complexes. The CD studies indicated that the combination with FA or TMP decreased the α -helix content of kafirin slightly. The shifts and intensity changes of UV–Vis, FTIR and fluorescence spectra confirmed the formations of complexes. Moreover, the molecular docking and molecular dynamics studies showed that hydrophobic interactions and hydrogen bonds played major roles in the formations of kafirin-FA and kafirin-TMP complexes, and the formations of complexes made kafirin structures more compact. This work is of great importance for further quality improvement in baijiu and alcoholic beverages.